Efficient Multi-Cloud Storage Using Online Dynamic Replication and Placement Algorithms for Online Social Networks - Ali Y. Aldailamy; Abdullah Muhammed; Nor Asilah Wati Abdul Hamid; Rohaya Lati; Waidah Ismail (IEEE Access, 2024)
Indexed by WOS/ Scopus